The ‘green island’ imaginary: media framing of Bali’s energy policy - Febriani, Nufian; Subiakto, Henri; Wahyudi, Irfan; Avicenna, Fitria (Jurnal Studi Komunikasi, 2026)
This study examined how the mass media depict the transition to renewable energy in Bali through the cultural imagination of the ‘green island’. Using a critical case study approach, this study combines media content analysis, interviews with journalists, policymakers, and community leaders, as well as a review of energy policies implemented between 2019 and 2024. The results show that state and corporate actors strategically adopt local cultural values, such as Tri Hita Karana, to legitimise energy policies. On the other hand, forms of community resistance rooted in customary and spiritual claims gain visibility but have limited political effectiveness because they are integrated into the dominant media narrative. The results of the study show that the ‘green island’ imagination functions as a symbolic mechanism that prioritises tourism-oriented development and political legitimacy over substantial community participation in Bali's energy governance.